MINANGKABAU LOCAL WISDOM-BASED EDUCATIONAL TOURISM AS AN EFFORT TO FOSTER CULTURAL IDENTITY AMONG THE YOUNGER GENERATION - Sri Rahayu; Faishal Yasin; Ade Pratama; Rinel Fitlayeni; Annisa Amini; Maulana Agiel Pratama (LPPM Universitas PGRI Sumatera Barat, 2025)
Minangkabau local wisdom-based educational tourism is an approach that integrates elements of education, recreation, and sustainable cultural preservation. Kubu Gadang Tourism Village in Padang Panjang City is a concrete example of the application of this concept through various traditional activities, such as making onde-onde, planting rice, playing traditional musical instruments, randai, traditional pacu upiah games, and making pupuik from rice stalks. These activities are not only tourist attractions, but also a means of contextual cultural learning for the younger generation because they can learn directly through real experiences, interactions with local communities, and appreciation of the traditional values that live in the community. This study aims to examine how Minangkabau local wisdom-based educational tourism can foster cultural identity among the younger generation. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that the involvement of young people in various educational tourism activities increases their knowledge, understanding, and appreciation of Minangkabau cultural values. In addition, these activities strengthen their sense of belonging, pride, and responsibility for their cultural identity, while encouraging the active participation of young people in efforts to preserve traditions. These findings indicate that Minangkabau-based educational tourism has great potential as an effective medium for transmitting cultural values to future generations in a sustainable manner amid the rapid pace of globalization. This study recommends strengthening collaboration between the community, government, educational institutions, and the private sector to develop more structured, innovative, and sustainable educational tourism programs so that Minangkabau cultural values can continue to be instilled in the younger generation, thereby strengthening, solidifying, and preserving their cultural identity.